2016
DOI: 10.1007/s12275-016-5379-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diversity and distribution of indigenous arbuscular mycorrhizal communities colonizing roots of two different winter cover crops in response to their root proliferation

Abstract: A clear understanding of how crop root proliferation affects the distribution of the spore abundance of arbuscular mycorrhizal fungi (AMF) and the composition of AMF communities in agricultural fields is imperative to identify the potential roles of AMF in winter cover crop rotational systems. Toward this goal, we conducted a field trial using wheat (Triticum aestivum L.) or red clover (Trifolium pratense L.) grown during the winter season. We conducted a molecular analysis to compare the diversity and distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 60 publications
1
14
1
Order By: Relevance
“…This could be one reason why P fertilizer input did not change the diversity of the AMF communities in tomato plants. Additionally, the impact of soil P on the diversity of AMF communities still remains a controversial subject, and the results could be related to P application rates [80], sampling times [83], host plant species [84,85], and agricultural management [86][87][88][89][90]. Our results were inconsistent regarding P fertilization on the diversity of AMF communities compared to previous reports.…”
Section: Effect Of P Fertilizer Level On the Amf Communities In Tomatcontrasting
confidence: 80%
“…This could be one reason why P fertilizer input did not change the diversity of the AMF communities in tomato plants. Additionally, the impact of soil P on the diversity of AMF communities still remains a controversial subject, and the results could be related to P application rates [80], sampling times [83], host plant species [84,85], and agricultural management [86][87][88][89][90]. Our results were inconsistent regarding P fertilization on the diversity of AMF communities compared to previous reports.…”
Section: Effect Of P Fertilizer Level On the Amf Communities In Tomatcontrasting
confidence: 80%
“…Genus-level abundances of OTUs assigned to the AM fungal group were dependent on cover crop identity, as well as CC Function. Previous studies have reported that cover crop effects on AM fungi, including biomass and community composition, seem to be dependent on cover crop species identity 19,21,23,25,[36][37][38][57][58][59] . Our study indicates that not only are the effects dependent on CC identity but they vary among genera of AM fungi.…”
Section: Discussionmentioning
confidence: 99%
“…(ITS) regions amplified from DNA extracts [21][22][23][24][25] . Overall, consistent patterns in cover crop species effects on AM fungal abundance and diversity have not been reported, with other factors such as soil type and season being more influential 26 .…”
mentioning
confidence: 99%
“…However, in our study we found spore production in vetch similar to that in fallow. Therefore, there is a need to clarify the effect of legume CCs on mycorrhization of the subsequent crop and elucidate which factors (e.g., root architecture, host preference, rhizobium symbiosis) could explain the lack of AMF enhancement in certain circumstances (Torrecillas et al, 2012;Higo et al, 2016). high values (81-91%) during the early maize stages and thus made subsequent increases difficult.…”
Section: Discussionmentioning
confidence: 99%